The association of limited or painful spinal range of motion with lumbar disc degeneration: the back complaints in older adults (BACE) study - Daniel Feller; Roxanne van den Berg; Wendy T. M. Enthoven; Edwin H. G. Oei; Sita M. Bierma-Zeinstra; Bart W. Koes; Alessandro Chiarotto (BMC Musculoskeletal Disorders)
Abstract Background We currently lack clear definitions for structural and symptomatic spinal osteoarthritis (OA). To define spinal OA and create diagnostic criteria for this condition, it is necessary to determine the relationship between clinical signs and symptoms of back pain and radiographic features of OA. Notably, recent studies suggest a defining sign of spinal OA could be a limited or painful spinal range of motion (ROM). Therefore, our objective was to assess the association between restricted or painful active spinal ROM, and multilevel structural features of lumbar disc degeneration (LDD) (i.e., disc space narrowing, osteophytes) on radiographs. Methods We used the baseline data from the’Back Complaints in Older Adults’ (BACE) study. The association between a limited or painful active spinal ROM, and multilevel disc space narrowing or osteophytes was assessed using multivariable logistic regression adjusted for age, mean pain intensity in the previous week, sex, BMI, and the Fear Avoidance Belief Questionnaire score. Primary analyses were performed on imputed datasets. Results We included 675 patients with a mean age of 66.52 years (SD 7.69). Limited latero-flexion (fingertip that at best reached halfway up the upper leg) was associated with increased odds of having multilevel osteophytes (OR 1.85; 95% CI: 1.13 to 3.01). However, a limited or painful ROM in other directions (i.e., rotation, ante-flexion) was not associated with multilevel osteophytes, and a limited or painful active ROM in any direction was found to have no association with multilevel disc space narrowing. Conclusions Our study indicates that a restricted ROM in latero-flexion could potentially be a defining sign in future definitions of symptomatic spinal OA. However, since our results partially differ from previous studies, further research is needed to explore the association between active ROM and LDD.